2018
DOI: 10.1159/000492269
|View full text |Cite
|
Sign up to set email alerts
|

Changes in MIDAS, Perceived Stress, Frontalis Muscle Activity and Non-Steroidal Anti-Inflammatory Drugs Usage in Patients with Migraine Headache without Aura following Ayurveda and Yoga Compared to Controls: An Open Labeled Non-Randomized Study

Abstract: Background: There has been a significant increase in the use of complementary and integrative medicine to provide long-term healing solutions in migraine headache patients. Knowing the limitations of conventional medical approach, the present study evaluated the influence of two Indian traditional systems of medicine on migraine-related disability, autonomic variables, perceived stress, and muscle activity in patients with migraine headache without aura. Methods: Thirty subjects recruited to the Ayurveda and Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Migraine disability was evaluated through a short and self-administered questionnaire thatquanti ed headache-related disability (MIDAS questionnaire). This questionnaire had 5 questions; the total score is calculated based on the number of days marked against each question [16]. The reliability and validity of the MIDAS questionnaire has been established in Iranian patients [17].…”
Section: Headache Daily Results and Disability Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine disability was evaluated through a short and self-administered questionnaire thatquanti ed headache-related disability (MIDAS questionnaire). This questionnaire had 5 questions; the total score is calculated based on the number of days marked against each question [16]. The reliability and validity of the MIDAS questionnaire has been established in Iranian patients [17].…”
Section: Headache Daily Results and Disability Assessmentmentioning
confidence: 99%
“…The reliability and validity of the MIDAS questionnaire has been established in Iranian patients [17]. Based on the total score, four grades were considered: Grade I with 0-5 score that meant little or no disability; Grade II with 6-10 score that meant mild disability; Grade III with 11-20 score that meant moderate disability; and Grade IV with more than 21 score that meant severe disability [16].…”
Section: Headache Daily Results and Disability Assessmentmentioning
confidence: 99%
“…The Migraine Disability Assessment (MIDAS) questionnaire was applied to rate the disability caused by headache in relation to professional and social life. It has seven questions related to work, social, family, and leisure activities in the last three months, besides analyzing the intensity and frequency of headache episodes 16,17 . The impact of headache frequency on quality of life was assessed by the Headache Impact Test (HIT-6).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study [ 3 ] suggested that the occurrence of migraine was related to the imbalance of the autonomic nervous system, and increasing parasympathetic (mainly including vagal) nerve activity could alleviate the symptoms of migraine [ 4 ]. However, there are only a few indirect ways to regulate the vagal nerve tension, such as breathing regulation and yoga [ 5 ].…”
Section: Introductionmentioning
confidence: 99%